Organizational culture towards patient safety in hospitals: A literature review - Rizky Khaeran; Nadia Putri Untiami; Donna Ndari Santoso Putri; Nirna Dwi Anggraini; Amanda Safitri; Siti Aisyah; Cahya Arbitera (PT WIM Solusi Prima, 2026)
Patient safety is a key indicator of hospital service quality and is strongly influenced by the organizational culture within healthcare settings. An organizational culture that promotes openness, collaboration, and continuous learning contributes to the creation of a safe care environment. This study aimed to examine the relationship between organizational culture and patient safety implementation in hospitals through a literature review. Literature searches were conducted using the Google Scholar, Springer, and Garuda databases. Eligible studies included full-text articles published in Indonesian or English between 2015 and 2024. The review of ten selected articles indicated that organizational culture positively influences patient safety. The dimensions that contributed most significantly to patient safety included teamwork, open communication, management support, organizational learning, and a non-punitive culture. However, staffing issues and inadequate non-punitive responses to errors remain challenges in patient safety implementation. Furthermore, a positive organizational culture was found to enhance incident reporting and strengthen healthcare workers’ commitment to patient safety. These findings suggest that fostering a supportive organizational culture is a strategic approach to improving the quality and safety of hospital care.